Low level laser therapy in the management of breast cancer-related lymphedema: protocol for a randomized controlled feasibility trial. (3rd September 2018) - Baxter, G. David; Liu, Lizhou; Petrich, Simone; Chapple, Cathy; Anders, Juanita J.; Tumilty, Steve
Abstract: Background : Breast cancer-related lymphedema (BCRL) is a prevalent long-term condition secondary to cancer treatment. BCRL impacts physical function, psychological health, and quality of life for patients who have survived breast cancer. Objectives: This study will assess the feasibility of a fully-powered randomized controlled trial investigating the effectiveness of low level laser therapy (LLLT), also known as photobiomodulation (PBM) therapy, as an adjunct treatment for managing BCRL. Methods: This study will be a pragmatic two-armed randomized controlled feasibility trial. Twenty female participants being treated for BCRL at the Dunedin Hospital, New Zealand, will be recruited over a 6-month window. Subject to informed consent, participants will be offered LLLT (PBM) in addition to their regular treatment for BCRL. Twelve treatments with laser therapy will continue for 6 weeks (twice weekly). Feasibility outcomes (recruitment rate, randomization rate, participant's adherence to the LLLT (PBM) treatment protocol, and participant retention rates) will be collected during the recruitment and intervention period. Participant satisfaction will be collected on completion of treatment intervention. Safety outcomes of LLLT (PBM) will be collected at each treatment visit. Clinical outcome measures (limb circumference, participant's perceived symptoms, psychological impacts, and activity disability) will be assessed at baseline, 6 and 12 weeks post-randomization. Conclusions: Results of this feasibility trial will inform the design and implementation of a future definitive randomized controlled trial, which will investigate the effectiveness of LLLT (PBM) for women with BCRL.